HLA-DR Expression Level in CD8+ T Cells Correlates With the Severity of Children With Acute Infectious Mononucleosis - Wang, Yun; Luo, Ying; Tang, Guoxing; Ouyang, Renren; Zhang, Minxia; Jiang, Yuhuan; Wang, Ting; Zhang, Xiwen; Yin, Botao; Huang, Jin; Wei, Wei; Huang, Min; et al. (Frontiers in Immunology, 2021)
Background: This study aimed to assess the host immune signatures associated with EBV infection and its clinical value in indicating the severity of children with acute infectious mononucleosis (IM). Methods: Twenty-eight pediatric patients with IM aged 3-8 years were enrolled. The immune-phenotypes and cytokine secretion capability of T cells were detected. Results: The percentages and absolute numbers of CD3+, CD8+ T cells were significantly increased in IM patients compared with HCs. The percentages of Naïve CD4+ and CD8+ T cells were decreased but with increased percentages of memory CD4+ and CD8+ T subsets. Our results showed the upregulation of active marker HLA-DR, TCR-αβ and inhibitory receptors PD-1, TIGIT in CD8+ T cells from IM patients, which suggested that effective cytotoxic T cells were highly against EBV infection. However, EBV exposure impaired the cytokine (IFN-γ, IL-2 and TNF-α) secretion capability of CD4+ and CD8+ T cells after stimulation with PMA/ionomycin in vitro. Multivariate analysis revealed that the percentage of HLA-DR+ CD8+ T cells was an independent prognostic marker for IM. The percentage of HLA-DR+ CD8+ T cells was significantly correlated with high viral load and abnormal liver function results. Conclusion: Robust expansion and upregulation of HLA-DR in CD8+ T cells, accompanied with impaired cytokine secretion were typical characteristics of children with acute IM. The percentage of HLA-DR+ CD8+ T cells might be used as a prominent marker not only for the early diagnosis, but also indicating the severity of IM.